Validação da escala de intenção de vingança online do consumidor para serviços - Cunha, Daniele Estivalete (2019)
This study aimed to perform cross-cultural adaptation and validation of the consumer online revenge intention scale for services by Obeidat et al. (2017) in the Brazilian context. To perform the translation and adaptation of the scale from English to Portuguese, the protocol suggested by Beaton et al. (2000), Hambleton (2005), Sireci et al. (2006), along with the additional steps used in the Borsa (2012) studies. In order for this instrument to be used in Brazil, its adaptation and validation was essential. Thus, the following steps were followed: Translation of the instrument; Synthesis of translations; Back translation of the instrument; Expert retranslation analysis; Evaluation of the instrument by the target audience; Pretest; and finally, Verification of psychometric properties. In order to meet the objectives proposed in this study, a descriptive, qualitative and quantitative research was conducted with 420 Brazilian consumers. It was found from the responses of the research participants that in both contexts of failure, respondents declared themselves dissatisfied, tending to manifest vengeful behaviors. From this, arouse negative emotions that may reflect in the public complaint, given the ease of use of the Internet and the reach of information in a short time. Finally, it is verified that the construct validity of the consumer online revenge intention scale for services has been confirmed, which can be applied in the Brazilian context. It is believed that the main contribution of the present thesis was the accomplishment of the cross-cultural adaptation and the validation of the consumer's online revenge intention scale for services, considering that this scale is a pioneer in the use of all the variables presented in set. Thus, the model by Obeidat et al. (2017) introduced new variables that explain consumers' choice to exercise online revenge, as well as identify the reasons and ways consumers use revenge when using the internet and social networks. Still, the validated model addresses the cognitive assessment process of online consumer revenge. By resuming the results of the study, some aspects that may contribute to the progress of scientific knowledge are highlighted. It is understood, therefore, that the study contributed to the validation of a model that not only focuses on personal assessments of service failure, but examines the influence of personal and situational factors after a service failure. In addition to not only connecting the cognitive component, but also emphasizing the emotional aspect. Using this tool will allow us to examine for the first time the state of secondary assessment in which consumers will evaluate the decision and the possibility of revenge online. Also, from the results of the studies that will apply this instrument, it will be possible to examine the complete cognitive, emotional, motivational and behavioral process of revenge. Future studies suggest a cross between profile variables and scale constructs. It is also indicated that a comparative analysis of the intention of online revenge taking into account the socio-demographic characteristics of the respondents. And finally, there is the need to investigate the reasons for rejection of some hypotheses in Brazil.